Concussion History and Balance Performance in Adolescent Rugby Union Players. Issue 5 (April 2021) - Matthews, Mark; Johnston, William; Bleakley, Chris M.; Davies, Richard J.; Rankin, Alan T.; Webb, Michael; Caulfield, Brian C.; Archbold, H.A.P.
Background: Sports-related concussion is a worldwide problem. There is a concern that an initial concussion can cause prolonged subclinical disturbances to sensorimotor function that increase the risk of subsequent injury. The primary aim of this study was to examine whether a history of sports-related concussion has effects on static and dynamic balance performance in adolescent rugby players. Hypothesis: Dynamic balance would be worse in players with a history of concussion compared with those with no history of concussion. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Male adolescent rugby players aged 14 to 18 years from 5 schools were recruited before the start of the 2018-2019 playing season. Participants completed questionnaires and physical tests, including dynamic Y balance and single-leg static balance (eyes closed) tests, while performing single and dual tasks. Dynamic balance was assessed using inertial sensor instrumentation. Dependent variables were normalized reach distance and the sample entropy (SEn) of the 3 axes ( x, y, and z ). Results: Of the 195 participants, 100 reported a history of concussion. Those with a history of concussion demonstrated higher SEn in all directions, with highest values during anterior (standardized mean difference [SMD], 0.4; 95% CI, 0.0-0.7; P = .027) and posteromedial (SMD, 0.5; 95% CI, 0.2-0.9; P = .004) reach directions compared with those with no history. There was no difference between groups (concussion history vs control) in traditional Y balance reach distances in the anterior or posteromedial directions or single-leg static balance during both single- ( P = .47) and dual-task ( P = .67) conditions. Conclusion: Adolescent rugby union athletes with a history of concussion had poorer dynamic balance during performance tasks compared with healthy controls. Static single-leg balance tests, either single or dual task, may not be sensitive enough to detect sensorimotor deficits in those with a history of concussion.